PERUBAHAN HARA DAN MIKROORGANISME PADA ULTISOL AKIBAT KASCING YANG BERBEDA - Oktanis Emalinda; Eti Farda Husin; Dina Puspita Rini (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2005)
This research was conducted in Soil Drying Room at Faculty of Agriculture Andalas University. Analysed in Soil Biology, Soil Chemic and Plant test and Disease Laboratories from August 2006 to February 2007. Aim of this research is to know the effect of substrate of vermicompost on population of soil microorganism on Ultisol. This experiment were designed on Complete Randomized Block Design in three treatment and three replicate. The treatment were different substrate of vermicompost, consisted of : without vermicompost, 10 ton/ha vermicompost with rice strow substrate and, 10 ton/ha vermicompost with dust wood. The result was showed, that vermicompost with rice strow could increase the growth rate of microorganism 320,14 % of fungi and 123,3 % bacteri. Used that this vermicompost can also increase soil nutritions (0,22 %, variable P 0,7 %; K-dd 0,04 me/100 g, Ca-dd 0,13 me/100 g and Mg-dd 0,08 me/100. Key word : vermicompost